Epigenetics: Recent Advances and Its Role in the Treatment of Alzheimer's Disease - Xiao, Xuewen; Liu, Xixi; Jiao, Bin (Frontiers in Neurology, 2020)
Objective: This review summarizes recent findings about the epigenetics of Alzheimer’s disease (AD) and provides therapeutic strategies for AD. Methods: We searched the following key words:’genetics’, ‘epigenetics’, ‘Alzheimer’s disease’, ‘DNA methylation’, ‘DNA hydroxymethylation’, ‘histone modifications’, ‘noncoding RNAs’, and ‘therapeutic strategies’ in PubMed. Results: In this review, we summarize recent studies of epigenetics in AD, including DNA methylation/hydroxymethylation, histone modifications, and non-coding RNAs. There were no consistent results of global DNA methylation/hydroxymethylation in relation to AD. Epigenetic genome-wide association studies showed that many differentially methylated sites were identified in AD. Several studies have investigated the role of histone modifications in AD; for example, histone acetylation decreased whereas H3 phosphorylation increased significantly in AD. In addition, noncoding RNAs, such as microRNA-16 and BACE1RSantisense transcript (BACE1-AS), were associated with the pathology of AD. These epigenetic changes provide us with novel insights into the pathogenesis of AD and may be the potential therapeutic strategies for AD. Conclusion: Epigenetics plays a crucial role in the pathogenesis of AD, including DNA methylation/hydroxymethylation, histone modifications, and noncoding RNAs, which provide potential therapeutic strategies for AD.